Progress toward resistance mechanism to epidermal growth factor receptor tyrosine kinase inhibitor - Zhang Lingling (Open Life Sciences, 2016)
The EGFR signaling pathway plays an important role in the occurrence and development of many malignant tumors. It has become a hot spot in the treatment of advanced cancer. At present, the small molecule epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), has been shown to advanced non-small-cell lung cancer (NSCLC), has a marked drug resistance or has developed one. The EGFR signaling pathway regulates a variety of cellular functions, and its drug resistance may be related to a number of signal transduction pathways, including drug resistance mutations, structural activation, downstream signaling pathway activation and VEGF expression changes, and so on. In this paper, we review the production mechanism of EGFR-TKI drug resistance.